2016
DOI: 10.1021/acsami.6b05271
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Functionalized Graphene by Radical Polymers for Graphene-Based High-Performance Cathode Materials

Abstract: Polymer-functionalized graphene sheets play an important role in graphene-containing composite materials. Herein, functionalized graphene sheets covalently linked with radical polymer, graphene-graft-poly(2,2,6,6-tetramethylpiperidin-1-oxyl-4-yl methacrylate) (G-g-PTMA), were prepared via surface-initiated atom transfer radical polymerization (SI-ATRP). A composite cathode with G-g-PTMA as major active material and reduced graphene oxide (RGO) as conductive additive was fabricated via a simple dispersing-depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 38 publications
3
69
0
Order By: Relevance
“…For example, an organic nanohybrid of lumiflavine (LF) and single‐walled carbon nanotubes (SWNTs) was reported as a free‐standing cathode with a high gravimetric energy density of up to 500 Wh kg −1 during a 25 min discharge . Alternatively, a composite material based on radical polymer‐ graft ‐functionalized graphene sheets (G‐ g ‐PTMA) and reduced graphene oxide (RGO) showed a high specific capacity of 466 mAh g −1 at a low current density of 0.2 A g −1 and a good rate performance as high as 228 mAh g −1 at a high current rate of 20.0 A g −1 . Unfortunately, a large amount of conductive carbon additives were used in the aforementioned examples, that is, almost 60 wt % of SWNTs in LF/SWNT and 85 wt % of graphene or RGO in G‐ g ‐PTMA/RGO, which significantly reduced the energy density of the batteries.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…For example, an organic nanohybrid of lumiflavine (LF) and single‐walled carbon nanotubes (SWNTs) was reported as a free‐standing cathode with a high gravimetric energy density of up to 500 Wh kg −1 during a 25 min discharge . Alternatively, a composite material based on radical polymer‐ graft ‐functionalized graphene sheets (G‐ g ‐PTMA) and reduced graphene oxide (RGO) showed a high specific capacity of 466 mAh g −1 at a low current density of 0.2 A g −1 and a good rate performance as high as 228 mAh g −1 at a high current rate of 20.0 A g −1 . Unfortunately, a large amount of conductive carbon additives were used in the aforementioned examples, that is, almost 60 wt % of SWNTs in LF/SWNT and 85 wt % of graphene or RGO in G‐ g ‐PTMA/RGO, which significantly reduced the energy density of the batteries.…”
Section: Introductionsupporting
confidence: 73%
“…[43] Alternatively,ac omposite material based on radical polymer-graft-functionalized graphene sheets (G-g-PTMA) and reduced graphene oxide (RGO) showedahigh specific capacity of 466 mAh g À1 at al ow current density of 0.2 Ag À1 and ag ood rate performance as high as 228 mAh g À1 at ah igh current rate of 20.0 Ag À1 . [44] Unfortunately,alarge amount of conductive carbon additives were used in the aforementioned examples, that is, almost 60 wt %o fS WNTsi nLF/SWNT and 85 wt %o fg raphene or RGO in G-g-PTMA/RGO, which significantly reduced the energy density of the batteries. When the loading of RGO was decreased to approximately 20 wt %i nt hree-dimensional graphene/polyimide composites (3D-RGO/PI), the capacity was only 175 mAh g À1 at al ow charge-discharge rate of 0.1C, which further decreased to less than 40 mAh g À1 when the rate was increasedt o5 C. [45] Therefore, how to achieve exceptional electrochemical performance with minimum utilization of electronically conductive carbon additives is still ac hallenge in the research of organic electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Charge and discharge do not reduce battery performance, among other advantages [6,7]. Various organic molecules have been examined toward obtaining organic-based electrodes, such as conducting polymers, electron-donor/acceptor molecules, metal-clusters, and organic radical molecules [8][9][10]. Radical polymers are composed of non-conjugated carbon backbones that contain pendant groups bearing reversible redox products of radical species The synthesis route to poly(TAm-co-SSS) and PTAm.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to decrease the solubility of the active material is to use cross-linked PTMA, creating a polymer network [12][13][14] or to graft PTMA on the conductive material. [12,[15][16][17] Non-covalent interactions between PTMA and the conductive material have also been considered with imidazolium [18] (cation-p interaction) and pyrene [19] (p-p stacking) as anchoring points to immobilize PTMA onto nanostructured carbon derivatives. Zhang et al recently reported a noncovalent interaction between a pyrene-functionalized PTMA and reduced graphene oxide (rGO).…”
Section: Introductionmentioning
confidence: 99%